Sonic Hedgehog Signaling Pathway Mediates Proliferation and Migration of Fibroblast-Like Synoviocytes in Rheumatoid Arthritis via MAPK/ERK Signaling Pathway - Liu, Fang; Feng, Xiao Xue; Zhu, Shang Ling; Huang, Hong Yu; Chen, Ying Di; Pan, Yun Feng; June, Rayford R.; Zheng, Song Guo; Huang, Jian Lin (Frontiers in Immunology, 2018)
Fibroblast-like synoviocytes (FLSs) are the major effector cells that lead to rheumatoid arthritis (RA) synovitis and joint destruction. Our previous studies showed that Sonic Hedgehog (SHH) signaling pathway is involved in aberrant activation of RA-FLSs and inhibition of SHH pathway decreases proliferation and migration of RA-FLSs. The objective of this study was to investigate if the SHH pathway mediates proliferation and migration of RA-FLS via the mitogen-activated protein kinases/extracellular signal-regulated kinases (MAPK/ERK) signaling pathway. SHH signaling was studied by using SHH agonist (Purmorphamine) and antagonist (Cyclopamine) targeting the Smoothened (SMO) in FLSs. U0126 was used to inhibit the MAPK/ERK signaling pathway. The phosphorylation level of ERK 1/2 (p-ERKl/2) was examined by western blot. Cell proliferation activity was detected using cell proliferation and cytotoxicity kit-8 (CCK8), and cell cycle distribution and S phase cells were evaluated by the flow cytometry. Cell migration was examined by Transwell assay. Results showed that, compared with the control group, Purmorphamine increased the expression of p-ERK1/2 protein in concentration-and time-dependent manners (P<0.01). Co-treated with Purmorphamine and U0126 or Cyclopamine both decreased the expression of p-ERK1/2 protein (P<0.01). RA-FLSs treated with Purmorphamine resulted in alteration of cell cycledistribution, increasing of S phase cells, cell proliferation activity, and migration cells compared to controls (P<0.01). However, the above phenomenon can be abolished by U0126 (P<0.05). The findings suggest that SHH signaling pathway mediates proliferation and migration of RA-FLS via MAPK/ERK pathway and may contribute to progression of RA. Targeting SHH signaling may have a therapeutic potential in patients with RA.